External Validation of the GREAT Score in Turkish Patients with Graves' Hyperthyroidism Treated with the Titration Regimen Method of Antithyroid Drugs: A Multicenter Study - Zuhur, Sayid Shafi; Elbuken, Gulsah; Yildiz, Ismail; Kadioglu, Pinar; Erol, Selvinaz; Sahin, Serdar; Altuntas, Yuksel (Georg Thieme Verlag Kg, 2019)
Recently, the Graves' Recurrent Events After Therapy score (GREAT) was proposed as a useful tool to predict relapse before starting antithyroid drugs (ATD) in patients with Graves' disease (GD). Therefore, we intended to assess the validity of the GREAT score in Turkish patients with GD, including patients who experienced a poorly controlled disease (multiple episodes of hyperthyroidism followed by euthyroidism or rarely hypothyroidism) during ATD dose titration. This is a retrospective multicenter study including 517 patients with the first episode of GD who were treated for at least 12 months. The patients were classified as relapse+poorly controlled disease (non-remission) and remission groups. During a median follow-up time of 35 months (12-144 months), 191 (37%) patients experienced a relapse, 136 (26.3%) a poorly controlled disease, and 190 (36.7%) remained in remission. Patients with non-remission disease tended to have significantly higher serum levels of TRAb, fT4, and fT3, and have larger goiter sizes on palpation at baseline, as compared with the remission group. Non-remission disease occurred in 12, 35, and, 53% of the patients falling into GREAT class I, II, and III, respectively (hazard ratio 2.56, 95% CI 2.02-3.51, p=0.012, and hazard ratio 3.54, 95% CI 2.12-5.91, p<0.001, for GREAT class II and III against class I, respectively). According to our study, the GREAT score is a useful tool to predict the risk of relapse as well as the occurrence of poorly controlled disease before starting treatment with ATDs.
Keywords: Graves' disease; relapse; antithyroid drugs; GREAT score